A Weighted Least Squares Consideration for IR-UWB Radar based Device-Free Object Positioning Estimation for Indoor Environment - Terence Jerome Daim; Razak Mohd Ali Lee (2019)
Impulse Radio Ultra-Wideband (IR-UWB) radar is a type of radar functioning based on UWB transmission technology that uses an exceedingly wide bandwidth low power impulse signal to continuously transmitting and receiving the impulse signal for object detection within a range. To date, most of the proposed Ultra-Wideband (UWB) transmission technology-based object positioning estimation systems for indoor environment depends on objects to be attached with an active UWB devices. In certain circumstances, it is ideal to track objects in passive manner without the requirement of any attached tracking devices or device-free object positioning estimation. IRUWB radar has shown promising utilization in realizing device-free object positioning estimation for indoor environment. With this motivation, in this paper a work on weighted least squares consideration for IR-UWB radar-based device-free object positioning estimation for indoor environment is presented.